Critical Discursive Psychology - Parker, I. author. aut Link
XIII, 303 p.
Keywords: This book introduces key issues and historical contexts in critical discursive research in psychology. It sets out methodological steps for critical readings of texts, arguments that can be made for qualitative research in academic settings, and arguments that could be made against it by critical psychologists.